Implementing validated technologies to improve governance & restoration in silvopastoral systems: Focus Group Discussion Report - Louhaichi, Mounir; Hassan, Sawsan; Ouled Belgacem, Azaiez; Jamel, Kailene (International Center for Agricultural Research in the Dry Areas, 2024)
It is a focus group discussion about the Livestock and Climate Initiative, aimed at assessing the impacts of silvopastoral system interventions on local communities in Tunisia. Conducted in July 2024, the discussions involved community members, ICARDA, and the General Directorate of Forests (DGF) in exploring economic outcomes, land use changes, social benefits, environmental impacts, and community empowerment. Key findings included significant economic advantages from integrating indigenous species like Sulla, which improved soil health and livestock production. Participants reported increased net revenue and enhanced community governance through the establishment of the Groupement de Développement Agricole (GDA). Environmental improvements were noted, alongside challenges such as limited job opportunities and access to quality seeds, highlighting the need for ongoing support. The initiative represents a promising model for sustainable development that can be replicated across the region.